DNA hypermethylation analysis in sputum of asymptomatic subjects at risk for lung cancer participating in the NELSON trial: argument for maximum screening interval of 2 years. Issue 3 (5th August 2016) - Hubers, A Jasmijn; Heideman, Daniëlle A M; Duin, Sylvia; Witte, Birgit I; de Koning, Harry J; Groen, Harry J M; Prinsen, Clemens F M; Bolijn, Anne S; Wouters, Mandy; van der Meer, Susanne E; Steenbergen, Renske D M; Snijders, Peter J F; et al.
Abstract : Aims: Lung cancer is the major contributor to cancer mortality due to metastasised disease at time of presentation. The current study investigated DNA hypermethylation of biomarkers RASSF1A, APC, cytoglobin, 3OST2, FAM19A4, PHACTR3 and PRDM14 in sputum of asymptomatic high-risk individuals from the NELSON lung cancer low-dose spiral CT screening trial to detect lung cancer at preclinical stage. Methods: Subjects were selected with (i) lung cancer in follow-up (cases; n=65), (ii) minor cytological aberrations (controls; n=120) and (iii) a random selection of subjects without cytological aberrations (controls; n=99). Median follow-up time for controls was 80 months. Cut-off values were based on high specificity to assess diagnostic value of the biomarkers. Results: RASSF1A may denote presence of invasive cancer because of its high specificity (93% (95% CI 89% to 96%); sensitivity 17% (95% CI 4% to 31%), with best performance in a screening interval of 2 years. The panel of RASSF1A, 3OST2 and PRDM14 detected 28% (95% CI 11% to 44%) of lung cancer cases within 2 years, with specificity of 90% (95% CI 86% to 94%). Sputum cytology did not detect any lung cancers. Conclusions: In a lung cancer screening setting with maximum screening interval of 2 years, DNA hypermethylation analysis in sputum may play a role in the detection of preclinical disease, but complementary diagnostic markers are needed to improve sensitivity.